2011
DOI: 10.5732/cjc.011.10018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in cancer: at the crossroads of life and death

Abstract: Mitochondrial processes play an important role in tumor initiation and progression. In this review, we focus on three critical processes by which mitochondrial function may contribute to cancer: through alterations in glucose metabolism, the production of reactive oxygen species (ROS) and compromise of intrinsic apoptotic function. Alterations in cancer glucose metabolism include the Warburg effect, leading to a shift in metabolism away from aerobic respiration toward glycolysis, even when sufficient oxygen is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 98 publications
1
101
0
Order By: Relevance
“…There are two known signaling pathways: the extrinsic pathway mediated by cell surface death receptors and the intrinsic one initiated in the mitochondria (Igney and DOI:http://dx.doi.org/10.7314/APJCP.2014.15.23.10495 Bufalin Induces Mitochondrial Pathway Mediated Apoptosis in Lung Adenocarcinoma Cells Krammer, 2002. Much more than the "powerhouse" of the cell, mitochondria also lies in the center of cell apoptotic pathways (Fogg et al, 2011). Often before the characteristic changes in nucleus, mitochondria has contributed to apoptosis through the remarkable transformation of morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…There are two known signaling pathways: the extrinsic pathway mediated by cell surface death receptors and the intrinsic one initiated in the mitochondria (Igney and DOI:http://dx.doi.org/10.7314/APJCP.2014.15.23.10495 Bufalin Induces Mitochondrial Pathway Mediated Apoptosis in Lung Adenocarcinoma Cells Krammer, 2002. Much more than the "powerhouse" of the cell, mitochondria also lies in the center of cell apoptotic pathways (Fogg et al, 2011). Often before the characteristic changes in nucleus, mitochondria has contributed to apoptosis through the remarkable transformation of morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that TERT displays role(s) beyond the ability to lengthen telomeres and it is of importance to improve our current knowledge about these potential extra-telomeric functions of TERT. The modulation of ROS production, mitochondrial respiration and apoptosis are indeed crucial mechanisms involved in many different diseases and play a key role in tumor progression (Antonsson, 2004;Fogg et al, 2011;Hanahan and Weinberg, 2011;Low et al, 2011;Sung et al, 2005;Vogelstein et al, 2000). However most of these extra-telomeric roles of TERT remain controversial thus highlighting the need to further study this field.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria hold a primary role in cell biology through its implication in energetic metabolism, production of reactive oxygen species (ROS) and also as a key regulator of apoptosis (Fogg et al, 2011;Low et al, 2011;Saretzki, 2009). The mitochondrial pathway of apoptosis, also known as the intrinsic pathway, leads to the release of apoptogenic proteins from the intermembrane space of mitochondria upon apoptotic stimuli which in turn results in the activation of caspase 9 through the formation of a protein complex called the apoptosome (Antonsson, 2004;Saelens et al, 2004;Yuan et al, 2011).…”
Section: Tert Oxidative Stress and Mitochondriamentioning
confidence: 99%
“…They play a vital role in cellular energy production, reactive oxygen species (ROS) generation and apoptosis (1). Recent evidence has also demonstrated that mitochondria are involved in tumor initiation and progression (2)(3)(4). In contrast to other organelles present in cells, mitochondria have their own genome, mitochondrial DNA (mtDNA), which is a double-stranded circular DNA of approximately 16.6 kb, encoding 37 genes, including 22 tRNA, 2 rRNA and 13 protein subunits of respiratory complexes.…”
Section: Introductionmentioning
confidence: 99%